Mengapa Pancasila Mirip dengan Komunisme? Perspektif Guru Gembul - Latif Palikal Isbah Isbah; Ahmad Faisal (AGUSPATI RESEARCH INSTITUTA, 2023)
- The purpose of this research is to find out Guru Gembul's perspective on the similarities that exist between communism and Pancasila. In this study report, a qualitative descriptive method was used by listening closely because the data source was obtained by listening to the oral narrative from Guru Gembul's YouTube channel entitled